Solid oxide electrolysis cell, method for producing same, and use thereof
Patent Information
- Application Number
- CN202311401194.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-10-26
AI Technical Summary
[0004]为此,本发明所要解决的技术问题在于克服现有技术中固体氧化物电解池在高温还原CO2中催化剂材料的碳沉积等问题
[0028](1)本发明所述的制备方法通过多步骤球磨及煅烧,赋予催化剂材料均匀的粒径和良好的烧结特性。其中球磨混合后的预烧结稳定了晶相结构,使得固体氧化物电解池制备形貌变化减小,颗粒之间的烧结程度减弱,营造更多的三相(反应气体,离子及电子)反应界面,从而提高固体氧化物电解池的稳定性。除此之外,稳定的晶体形貌可以维持钙钛矿氧化物中掺杂的过渡族元素价态转化平衡,进而稳定高CO气氛下的抗积碳能力。
Smart Images

Figure CN117403253B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical technology, and particularly relates to a solid oxide electrolytic cell, its preparation method, and its application. Background Technology
[0002] Solid oxide electrolyzers (SOECs) represent the reverse reaction process of fuel cells. These devices utilize metal oxides throughout, offering rapid reaction rates and environmental friendliness, effectively avoiding the problems associated with liquid electrolytes in other types of fuel cells. Furthermore, they exhibit extremely high reaction rates and energy conversion efficiency, and the reduction in polarization under high-temperature operating conditions further lowers the energy consumption required for electrolysis. When combined with renewable energy sources, this technology holds immense potential in the green energy sector.
[0003] Solid oxide electrolysis (SOI) technology, which uses CO2 as a feed gas, is simple to operate, requires minimal equipment, produces a single product, and boasts high selectivity (~100%). It has practical application significance in alleviating the environmental problems caused by rising CO2 levels worldwide. However, in CO2 reduction to CO processes, to ensure stable operation of the electrolyzer, it is typically operated only under low CO partial pressure conditions, resulting in extremely low conversion rates and a small proportion of desired product. This leads to increased production costs in subsequent product separation and purification processes. Furthermore, operation under high CO partial pressure can cause the catalyst to induce the Boudouard reaction due to excessively high CO concentrations. The occurrence of CO partial pressure leads to carbon buildup and a significant increase in voltage. Therefore, improving the activity and stability of catalyst materials under high CO partial pressure to reduce the production and purification costs of CO has always been a key research focus. Summary of the Invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem of carbon deposition in catalyst materials during high-temperature CO2 reduction in the prior art using solid oxide electrolytic cells.
[0005] To address the aforementioned technical problems, this invention provides a solid oxide electrolytic cell, its preparation method, and its application.
[0006] The first objective of this invention is to provide a method for preparing a solid oxide electrolytic cell, comprising the following steps:
[0007] S1. Compound A and compound B are ball-milled, pre-sintered, and ball-milled to disperse them. Then, a pore-forming agent is added and ball-milled to create pores to obtain a mixed powder. The mass ratio of compound A to compound B is 5-7:3-5.
[0008] The chemical formula of compound A is A 1-x B x M 1-yN y O z+δ Where A is selected from La, Pr or Sr, B is selected from Sr, Ba or Ca, M and N are independently selected from Co, Fe, Ni, Cu or Mo; 0≤x≤0.5, 0≤y≤1, z is selected from 3, 4, 6 or 7;
[0009] The chemical formula of compound B is (Ce 1-p Gd p )O 1.95 Where 0.1≤p≤0.2;
[0010] S2. Add mixture A to the mixed powder described in S1 and ball mill, then add mixture B and continue ball milling to obtain a mixed slurry; the mixture A includes 10-20 parts by weight of polyvinyl butyral (PVB), 60-75 parts by weight of terpineol, and 3-7 parts by weight of triethanolamine (TEA); the mixture B includes 80-90 parts by weight of dioctyl phthalate (DOP) and 5-10 parts by weight of butanol;
[0011] S3. The mixed slurry described in S2 is applied to the upper and lower sides of the solid oxide electrolyte by screen printing or coating to form a cathode layer and an anode layer, and then calcined to obtain the solid oxide electrolytic cell.
[0012] In one embodiment of the present invention, in S1, compound A has a perovskite crystal phase and compound B has a fluorite crystal phase. The fluorite phase is used to improve the thermal expansion compatibility between the catalyst and the electrolyte separator and to improve the ionic conductivity of the system, thereby increasing the reaction interface.
[0013] In one embodiment of the present invention, in S1, the pre-sintering temperature is 950℃-1100℃, the time is 1h-3h, and the heating rate is 1℃ / min-3℃ / min. This is used to remove organic matter and moisture from the powder, promoting a more uniform particle morphology, chemical structure, and distribution, resulting in more complete sintering after subsequent electrode coating.
[0014] In one embodiment of the present invention, in S1, the pore-forming agent is selected from polymethyl methacrylate and / or starch; the amount of the pore-forming agent is 5%-20% of the total mass of compound A and compound B, which improves the gas reaction interface and transport capacity.
[0015] In one embodiment of the present invention, in S1, the rotational speed of ball milling mixing, ball milling dispersion and ball milling pore formation is independently 160 r / min-230 r / min, and the time is independently 6 h-20 h.
[0016] In one embodiment of the present invention, in S1, a ball milling aid is also added during the ball milling process.
[0017] Furthermore, the ball milling aid is selected from one or more of ethanol, methanol, and isopropanol.
[0018] In one embodiment of the present invention, in S2, the rotational speed of the ball mill is 160 r / min-400 r / min, and the total time is 6 h-20 h.
[0019] In one embodiment of the present invention, in S2, the mass ratio of the mixed powder, mixture A, and mixture B is 9-11:8-11:1-4. The addition of these mixtures ensures uniform dispersion of the ball-milled catalyst, which is beneficial for the distribution of the reaction interface in the catalyst layer. The stepwise addition of mixtures A and B effectively improves the dispersibility and flowability of the slurry, thereby increasing the reaction interface, improving the surface smoothness of the catalyst and the adhesion between the solid oxide electrolyte and the catalyst, enhancing ion and electron transport between the solid oxide electrolyte and the catalyst layer, resulting in a more uniform current distribution and higher overpotential resistance.
[0020] In one embodiment of the present invention, in S3, the solid oxide electrolyte is selected from one or more of scandium-stabilized zirconium oxide (SSZ), yttrium-stabilized zirconium oxide (YSZ), and lanthanum-strontium-gallium-magnesium oxide.
[0021] In one embodiment of the present invention, in S3, the calcination temperature is 1100℃-1200℃, the time is 1h-3h, and the heating rate is 1℃ / min-3℃ / min.
[0022] In one embodiment of the present invention, in S3, the downward side is calcined using a medium that does not react with compound A.
[0023] Furthermore, the medium is selected from one or more of aluminum oxide, cerium oxide, and magnesium oxide.
[0024] A second objective of this invention is to provide a solid oxide electrolytic cell prepared by the aforementioned preparation method.
[0025] A third objective of this invention is to provide an application of the aforementioned solid oxide electrolytic cell in the reduction of CO2 to produce CO.
[0026] In one embodiment of the present invention, the operating temperature of the solid oxide electrolytic cell in the application is 600℃-900℃.
[0027] The technical solution of the present invention has the following advantages compared with the prior art:
[0028] (1) The preparation method described in this invention, through multi-step ball milling and calcination, imparts uniform particle size and good sintering characteristics to the catalyst material. The pre-sintering after ball milling stabilizes the crystal structure, reducing morphological changes in the solid oxide electrolytic cell and weakening the sintering degree between particles, thus creating more three-phase (reactant gas, ion, and electron) reaction interfaces and improving the stability of the solid oxide electrolytic cell. Furthermore, the stable crystal morphology can maintain the valence state transformation equilibrium of the transition elements doped in the perovskite oxide, thereby stabilizing the anti-carbon deposition ability under high CO atmosphere.
[0029] (2) In specific applications, the solid oxide electrolytic cell of the present invention uses CO2 as the raw material gas and introduces CO(P) at different partial pressures. CO The CO concentration in the feed gas was increased by adjusting the concentrations to 0.3 atm, 0.4 atm, 0.5 atm, and 0.6 atm respectively to measure the anti-carbon deposition performance of the prepared solid oxide electrolyzer, which achieved extremely high CO partial pressure tolerance (~0.85±0.03 atm). During CO2 reduction, the single-pass conversion rate reached as high as 77%, and the energy efficiency reached as high as 74%, achieving a performance within ~0.80 atm. CO Stable operation under partial pressure for ~300 hours. Attached Figure Description
[0030] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein:
[0031] Figure 1 The La pre-sintered product in Example 3 of this invention 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3+δ With Gd 0.1 Ce 0.9 O 1.95 XRD patterns of the mixed materials;
[0032] Figure 2 This is a SEM image of the solid oxide electrolytic cell of Example 3 of the present invention;
[0033] Figure 3 This is a SEM image of the solid oxide electrolytic cell of Comparative Example 3 of the present invention;
[0034] Figure 4 This is a comparison chart of the electrolytic catalyst performance of the electrolytic cell in Test Example 3 of the present invention;
[0035] Figure 5 This is a current-time comparison curve of the electrolytic cell in Test Example 4 of the present invention;
[0036] Figure 6 The air outlet P of Test Example 4 of the present invention CO A scatter plot of the relationship between the percentage and Faraday efficiency and current density along the dual Y-axis;
[0037] Figure 7 This is a graph showing the relationship between the highest single-pass conversion rate and current density of the electrolytic cell in Test Example 5 of the present invention under different CO inlet gas concentrations.
[0038] Figure 8 This is a graph showing the stability data of the electrolytic cell in Test Example 6 of the present invention. Detailed Implementation
[0039] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0040] In this invention, unless otherwise stated, A 1-x B x M 1-y N y O z+δ and (Ce 1-p Gd p )O 1.95 Purchased from Ningbo Sofuren Energy Technology Co., Ltd.
[0041] In this invention, unless otherwise stated, the materials were purchased from Aladdin Reagents Company.
[0042] Example 1
[0043] The solid oxide electrolytic cell and its preparation method of the present invention specifically include the following steps:
[0044] S1, Pr 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ and Gd 0.1 Ce 0.9 O 1.95 The powder was mixed at a mass ratio of 6:4 and ball-milled (160 r / min, 20 h). The mixed powder was then placed in an alumina crucible and heated to 950 °C at a heating rate of 2 °C / min for 3 h for pre-sintering. The pre-sintered powder was then ball-milled (200 r / min, 10 h), and then 8% (by weight of powder) of polymethyl methacrylate microspheres were added for ball milling to create pores (160 r / min, 6 h) to obtain a mixed powder. Ethanol was also added during the ball milling process.
[0045] S2. Add mixture A (20 parts polyvinyl butyral, 75 parts terpineol, and 5 parts triethanolamine) to the mixed powder of S1 and ball mill (400 r / min, 10 h). Then add mixture B (90 parts dioctyl phthalate and 10 parts butanol) and continue ball milling for 10 h to obtain a mixed slurry. The mass ratio of the mixed powder, mixture A, and mixture B is 9:9:2.
[0046] S3. The mixed slurry of S2 is screen-printed onto the upper and lower sides of yttrium stabilized zirconium oxide (YSZ, with GDC separator already coated) to form a cathode layer and an anode layer. The anode layer is placed on a calcining alumina medium that does not react with the material and heated to 1150℃ for 1 hour at a heating rate of 2℃ / min to obtain a solid oxide electrolytic cell.
[0047] Example 2
[0048] S1, Pr 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ and Gd 0.1 Ce 0.9 O 1.95 The powder was mixed at a mass ratio of 7:3 and ball-milled (160 r / min, 20 h). The mixed powder was then placed in an alumina crucible and heated to 950 °C at a heating rate of 2 °C / min for 3 h for pre-sintering. The pre-sintered powder was then ball-milled (200 r / min, 10 h), and then 8% (by weight of powder) of polymethyl methacrylate microspheres were added for ball milling to create pores (160 r / min, 6 h) to obtain a mixed powder. Ethanol was also added during the ball milling process.
[0049] S2. Add mixture A (20 parts polyvinyl butyral, 75 parts terpineol, and 5 parts triethanolamine) to the mixed powder of S1 and ball mill (400 r / min, 10 h). Then add mixture B (90 parts dioctyl phthalate and 10 parts butanol) and continue ball milling for 10 h to obtain a mixed slurry. The mass ratio of the mixed powder, mixture A, and mixture B is 9:9:2.
[0050] S3. The mixed slurry of S2 is screen-printed onto the upper and lower sides of yttrium stabilized zirconium oxide (YSZ, with GDC separator already coated) to form a cathode layer and an anode layer. The anode layer is placed on a calcining alumina medium that does not react with the material and heated to 1150℃ for 1 hour at a heating rate of 2℃ / min to obtain a solid oxide electrolytic cell.
[0051] Example 3
[0052] S1, La 0.6Sr 0.4 Co 0.2 Fe 0.8 O 3+δ and Gd 0.2 Ce 0.8 O 1.95 The powder was mixed at a mass ratio of 6:4 and ball-milled (210 r / min, 10 h). The mixed powder was then placed in an alumina crucible and pre-sintered at 950 °C for 3 h at a heating rate of 3 °C / min. The pre-sintered powder was then ball-milled (160 r / min, 10 h), and then 15% (by weight of the powder) of polymethyl methacrylate microspheres were added for ball milling to create pores (210 r / min, 20 h) to obtain a mixed powder. Ethanol was also added during the ball milling process.
[0053] S2. Add mixture A (10 parts polyvinyl butyral, 75 parts terpineol, and 5 parts triethanolamine) to the mixed powder of S1 and ball mill (300 r / min, 5 h). Then add mixture B (90 parts dioctyl phthalate and 10 parts butanol) and continue ball milling for 10 h to obtain a mixed slurry. The mass ratio of the mixed powder, mixture A, and mixture B is 11:8:4.
[0054] S3. The mixed slurry of S2 is screen-printed onto the upper and lower sides of yttrium stabilized zirconium oxide (YSZ, with GDC separator already coated) to form a cathode layer and an anode layer. The anode layer is placed on a calcining alumina medium that does not react with the material and heated to 1150℃ for 2 hours at a heating rate of 3℃ / min to obtain a solid oxide electrolytic cell.
[0055] Comparative Example 1
[0056] The process is basically the same as in Example 3, except that the firing medium is a zirconium oxide ceramic plate containing Zr.
[0057] Comparative Example 2
[0058] The process is basically the same as in Example 3, except that the ball milling speed is 120 r / min.
[0059] Comparative Example 3
[0060] It is basically the same as Example 3, except that pre-sintering is not performed.
[0061] Comparative Example 4
[0062] Commercial Ni-YSZ electrode-supported electrolytic cells.
[0063] Test Example 1
[0064] Based on Example 3, the pre-sintered La 0.6 Sr 0.4Co 0.2 Fe 0.8 O 3+δ With Gd 0.1 Ce 0.9 O 1.95 The mixed materials were subjected to XRD tests, and the results are as follows: Figure 1 As shown, from Figure 1 It can be seen that La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3+δ and Gd 0.2 Ce 0.8 O 1.95 The superposition of peaks proves that La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3+δ With Gd 0.2 Ce 0.8 O 1.95 No side reactions occurred during the mixing.
[0065] Test Example 2
[0066] Electron microscopy characterization was performed on the solid oxide electrolytic cells of Example 3 and Comparative Example 3, and the results are as follows: Figure 2-3 As shown, from Figure 2-3 It can be seen that the particle size and pore distribution of Example 3 are more uniform than those of Comparative Example 2, which is beneficial to gas mass transfer and current distribution.
[0067] Test Example 3
[0068] Constant current step tests (0.3A, 0.5A, 0.7A, 0.9A, 1.1A, etc.) were performed on the solid oxide electrolytic cells of Examples 2-3 and Comparative Examples 1-3, and the results are as follows. Figure 4 As shown. From Figure 4 It can be seen that the solid oxide electrolytic cells of Examples 2-3 have better stability and resistance to carbon deposition than Comparative Example 3. A comparison between Example 3 and Comparative Example 1 shows that optimization of the calcining medium significantly improves performance. A comparison between Example 3 and Comparative Example 2 reveals that the ball milling speed affects the uniformity of catalyst material dispersion, leading to performance degradation.
[0069] Test Example 4
[0070] Constant current electrolysis tests were conducted on the electrolytic cells of Example 3 and Comparative Example 4, and the product-to-feed gas ratio was analyzed by gas chromatography. In these tests, air was introduced at a flow rate of 100 sccm / min at the anode, and a mixture of CO2 and CO with different proportions (0.3 atm P) was introduced at the cathode. CO 0.7 atm P CO20.4 atm P CO 0.6 atm P CO2 0.5 atm P CO 0.5 atm P CO2 0.6 atm P CO 0.4 atm P CO2 A reduction reaction was conducted to test the carbon deposition resistance at 800℃. During the reaction, CO2 was reduced to CO at the cathode, and oxygen evolution occurred at the anode via transported oxygen ions. The testing equipment was a Metrohm Autolab electrochemical workstation, and the testing method used constant current mode. The initial total current intensity was 0.3A, with each step current increasing by 0.2A. The results are as follows: Figure 5-6 As shown. From Figure 5-6 It can be seen that the solid oxide electrolyzer of Example 3 achieved a CO concentration of 0.88 atm and was able to operate, which is far superior to the performance of the commercial Ni-YSZ electrode-supported electrolyzer (0.65 atm P). CO The rapid voltage decay demonstrates the excellent anti-carbon deposition performance of solid oxide electrolyzers, which helps reduce the difficulty of separating CO products and promotes commercial applications.
[0071] Test Example 5
[0072] Constant current tests were conducted on the electrolytic cells of Example 3 and Comparative Example 4 at different CO inlet gas concentrations. The flow rate was determined by a gas flow meter, with the total flow rate kept constant at 50 sccm / min, according to (0.3 atm P) CO 0.7 atm P CO2 0.4 atm P CO 0.6 atmP CO2 0.5 atm P CO 0.5 atm P CO2 0.6 atm P CO 0.4 atm P CO2 ) Perform flow rate allocation, and the test data processing results are as follows Figure 7 As shown. From Figure 7 It can be seen that, under different inlet CO concentrations, the electrolytic cell of Example 3 has a single-pass conversion rate (the ratio of generated CO to CO2 inlet flow rate) that is more than double that of the electrolytic cell of Comparative Example 4. The electrolytic cell of Example 3 achieves this at 700 mA / cm². -2 At the current density, the highest single-pass conversion rate can reach 77%, which proves the practical application value of the solid oxide electrolytic cell prepared by the method of this application.
[0073] Test Example 6
[0074] The electrolytic cell of Example 3 was subjected to constant current electrolysis test. With an inlet gas concentration of PCO of 0.67 atm, the electrolysis rate was 0.22 A / cm³. 2 The constant current test, and the test data processing results are as follows: Figure 8 As shown. From Figure 8 It can be seen that at 0.8 atm P CO The material operated stably for 300 hours at the specified gas concentration, demonstrating its excellent commercial performance.
[0075] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a solid oxide electrolytic cell, characterized in that, Includes the following steps, S1. Compound A and compound B are ball-milled, pre-sintered, and ball-milled to disperse them. Then, a pore-forming agent is added and ball-milled to create pores, resulting in a mixed powder. The mass ratio of compound A to compound B is 5-7:3-5. The pre-sintering temperature is 950℃-1100℃, the time is 1h-3h, and the heating rate is 1℃ / min-3℃ / min. The chemical formula of compound A is A 1-x B x M 1-y N y O z+δ Where A is selected from La or Pr, B is selected from Sr, M and N are independently selected from Co, Fe or Ni; 0≤x≤0.5, 0≤y≤1, z is selected from 3; The chemical formula of compound B is (Ce 1-p Gd p )O 1.95 Where 0.1≤p≤0.2; S2. Add mixture A to the mixed powder described in S1 and ball mill, then add mixture B and continue ball milling to obtain a mixed slurry; the mixture A, by weight, includes 10-20 parts of polyvinyl butyral, 60-75 parts of terpineol, and 3-7 parts of triethanolamine; the mixture B, by weight, includes 80-90 parts of dioctyl phthalate and 5-10 parts of butanol; the ball milling speed is 160 r / min-400 r / min, and the total time is 6 h-20 h; S3. The mixed slurry described in S2 is placed on the upper and lower sides of the solid oxide electrolyte by screen printing or coating to form a cathode layer and an anode layer, and then calcined to obtain the solid oxide electrolytic cell; the calcining medium used in the calcination process is alumina.
2. The method for preparing a solid oxide electrolytic cell according to claim 1, characterized in that, In S1, the pore-forming agent is selected from polymethyl methacrylate and / or starch; the amount of the pore-forming agent is 5%-20% of the total mass of compound A and compound B.
3. The method for preparing a solid oxide electrolytic cell according to claim 1, characterized in that, In S1, the rotation speeds for ball milling mixing, ball milling dispersion, and ball milling pore formation are independently 160 r / min to 230 r / min, and the time is independently 6 h to 20 h.
4. The method for preparing a solid oxide electrolytic cell according to claim 1, characterized in that, In S2, the mass ratio of the mixed powder, mixture A, and mixture B is 9-11:8-11:1-4.
5. The method for preparing a solid oxide electrolytic cell according to claim 1, characterized in that, In S3, the solid oxide electrolyte is selected from one or more of scandium-stabilized zirconium oxide, yttrium-stabilized zirconium oxide, and lanthanum-strontium-gallium-magnesium oxide.
6. The method for preparing a solid oxide electrolytic cell according to claim 1, characterized in that, In S3, the calcination temperature is 1100℃-1200℃, the time is 1h-3h, and the heating rate is 1℃ / min-3℃ / min.
7. A solid oxide electrolytic cell prepared by the preparation method according to any one of claims 1-6.
8. The application of the solid oxide electrolytic cell according to claim 7 in the reduction of CO2 to produce CO.
Citation Information
Patent Citations
Novel synergistic process and recipe for fabrication of a high integrity membrane electrode assembly of solid oxide fuel cell
US20090068373A1